Nordic Working Life Research - Continuity and Renewal - Hvid, Helge; Bergholm, Tapio; Gonäs, Lena; Juul, Ida; Kamp, Annette; Karlsson, Jan Ch.; Kasvio, Antti; Klemsdal, Lars; Salomon, Robert H.; Skorstad, Egil J. (Nordic Journal of Working Life Studies, 2011)
Working life research does not have clear boundaries; however its focus is quite clear: Changes in working life and how these changes affect qualifications, health, occupations, innovation, the economy, identity, social orientation and culture. The density of working life research is quite high in the Nordic countries, and this research has always been involved in the development of the Nordic welfare societies in which the development of work has been one important factor. In this article working life research is presented in its historical contexts, emphasizing the welfare challenges to which the research has been related. The challenges and tensions related to the research are not presented as being simply internal to the research work, they also reflect challenges and tensions in working life and institutions that are supposed to support working life. Current controversies in working life research in the four Nordic countries will briefly be presented, and institutional challenges for the research in the four countries will be exemplified. Finally, the aims of the journal will be outlined.